THE DEVELOPMENT OF ANIMATION AND SIMULATION BASED LEARNING MEDIA IN THE COSMOGRAPHY COURSE - Suherdiyanto Suherdiyanto; Adhitya Prihadi (GeoEco, 2024)
Learning media is a tool that can be used to facilitate the process of conveying knowledge in education. Media is very useful for describing subjects to make them clearer, shorter and more enjoyable. Because the availability and need for smartphones in universities is a priority, the use of animation and simulation-based learning media is an option. The objectives of this research are 1) to determine the level of suitability of material experts in animation and simulation-based learning media, 2) to determine the suitability of experts in animation and simulation-based learning media, 3) to determine the response to the use of animation and simulation-based learning media in cosmography courses. The method used in this research is a Research and Development approach (R & D) using a 4-D model (Four-D Models) which consists of four stages (Define, Design, Development, and Dissemination). The results of the research show: 1) the average assessment of material aspects by material experts obtained a score of 79%. The results of the assessment were in the range of 62.50, score ≤ 81.25% in the feasible category, 2) The average assessment by experts The media obtained a score of 81%, the assessment results were in the range of 81.25<score ≤100% in the very feasible category. 3) The response to using the animation and simulation-based learning media resulted in a calculation of 77.2 in the good category. These results can help learning activities, but there are obstacles from field conditions, as well as equipment and networks that must be developed further.